Vitamin K2 Enhances Fat Degradation to Improve the Survival of C. elegans - Qu, Zhi; Zhang, Lu; Huang, Wei; Zheng, Shanqing (Frontiers in Nutrition, 2022)
The beneficial effects of vitamin K (VK) on various chronic age-related syndromes have generally been considered dependent on its antioxidant effects. However, due to the distinct bioavailability and biological activities of VKs, exactly which of these activities and by what mechanisms they might act still need to be elucidated. In this study, we found that VK2 can extend the lifespan of C. elegans and improve the resistance to pathogen infection, heat stress and H2O2-induced inner oxidative stress . Importantly, the roles of VK2 on aging and stress resistance were shown to be dependent on enhanced fat metabolism and not due to its antioxidant effects. Moreover, the genes related to fat metabolism that were up-regulated following VK2 treatment play key roles in improving survival. Obesity is a leading risk factor for developing T2DM, and taking VKs has been previously considered to improve the insulin sensitivity associated with obesity and T2DM risk. However, our results showed that VK2 can significantly influence the expression of genes related to fat metabolism, including those that regulate fatty acid elongation, desaturation, and synthesis of fatty acid-CoA. VK2 enhanced the fatty acid β-oxidation activity in peroxisome to degrade and digest fatty acid-CoA. Our study implies that VK2 can enhance fat degradation and digestion to improve survival, supporting the effectiveness of VK2-based medical treatments. VK2 is mainly produced by gut bacteria, suggesting that VK2 might facilitate communication between the gut microbiota and the host intestinal cells to influence fat metabolism.